A CRPA array with dual‐mode patch antenna elements for GPS applications. Issue 5 (8th April 2018) - Rezazadeh, Navid; Shafai, Lotfollah
Abstract: A controlled reception pattern antenna (CRPA) array consisting of three dual‐mode microstrip patch antennas is designed and investigated for GPS interference mitigation applications. Each dual‐mode element consists of a dominant‐mode disk patch antenna encircled by a dual‐polarized shorted ring patch antenna. The measured input and radiation parameters of a prototype array are presented. The null‐steering performance of the array is demonstrated using a simple adaptive algorithm and is shown to be superior to the conventional planar arrays.